PEROVSKITE SOLAR CELLS YANG STABIL UDARA DAN EFISIEN MENGGUNAKAN NANOSTRUKTUR ZnO SEBAGAI ELEKTRON TRANSPORT MATERIAL - Herna Herna; Farhan Lutfi; Ebigail Nur Tabita Tambunan; Yessi Meinarti; Ari Sulistyo Rini (Universitas Riau, 2022)
The latest generation of photovoltaic cells are perovskite-based solar cells that can be fabricated through a simple and affordable process using high-efficiency solar power. This review also present zinc oxide (ZnO) adopted as an electron transport material (ETM) layer in the planar perovskitesolar cells due to its simple shynthesis and excellent electrical properties. ZnO ETM in conventional perovskite. Doping Aluminium (Al) with ZnO (AZO) was used the organic cation (CH3NH+3) of perovskite. The AZO ETM was prepared by spin coating technique with AZO sol-gel 0, 0.5, 1, 1.5, 2, 2.5 and 3% Al doping. The perovskite solar cells with AZO ETM above 1.5% Al doping exhibits better and stable the performance cells because doing so can encourage the charge transporting and match the band energy with MAPl3 compared to pure ZnO.